Proteases and caspase-like activity in the yeast Saccharomyces cerevisiae. (21st September 2011) - Wilkinson, Derek; Ramsdale, Mark
Abstract : A variety of proteases have been implicated in yeast PCD (programmed cell death) including the metacaspase Mca1 and the separase Esp1, the HtrA-like serine protease Nma111, the cathepsin-like serine carboxypeptideases and a range of vacuolar proteases. Proteasomal activity is also shown to have an important role in determining cell fate, with both pro- and anti-apoptotic roles. Caspase 3-, 6- and 8-like activities are detected upon stimulation of yeast PCD, but not all of this activity is associated with Mca1, implicating other proteases with caspase-like activity in the yeast cell death response. Global proteolytic events that accompany PCD are discussed alongside a consideration of the conservation of the death-related degradome (both at the level of substrate choice and cleavage site). The importance of both gain-of-function changes in the degradome as well as loss-of-function changes are highlighted. Better understanding of both death-related proteases and their substrates may facilitate the design of future antifungal drugs or the manipulation of industrial yeasts for commercial exploitation.